Curd product from peanut milk (Arachis hypgaea L.) - Llamas, Normita M.; De Leon, Sonia Y. (1977)
Fresh mature hand peeled peanuts (Arachis hypgaea L.) were used as raw material for the peanut milk. The extracted peanut milk was then used as a starting material in developing a curd product. The first phase of of the study involved the determination of the best soaking condition for the peanut milk. The effect of soaking condition for the peanut milk. The effect of soaking the raw material in water before the extraction of the milk was tested for four separate samples. The first sample was not soaked while the others were soaked for 6, 12 and 24 hours. The recovery of the milk increased as time of soaking was increased from 89.50% for the unsoaked sample to 89.70, 90.40 and 92.60% for 6.12 and 24 hours samples respectively. Protein content of the milk was maximum at 12-hr soaking time, being 2.4 grams per 200 ml of milk. Further increase in soaking period tended to decrease the protein content. The density was decreased by soaking treatment while specific gravity and pH were not very much affected. Unsoaked sample was the most inferior of all in terms of yield, recovery and protein. Sample S2, the one soaked for 12 hours was chosen the best among the samples of peanut milk. The second phase dealt on the development of a curd product out of of extracted peanut milk. The use of a chemical coagulant, calcium sulfate,was employed. Four levels of calcium sulfate was tested namely 0, 3, 5 and 10%. The samples with 5% calcium sulfate had the highest yield, best moisture content, pH and general acceptability.
Thesis (B.S.)--University of the Philippines, Quezon City.
Typescript.
Keywords: Peanut milk